ANALISIS KESULITAN MENYELESAIKAN SOAL TRIGONOMETRI SISWA SMA NEGERI 3 PAREPARE - Nurhadiyah Nurhadiyah (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2025)
This research is a qualitative study which aims to describe the difficulties in solving trigonometry problems for students in class XI MIPA 1 UPT SMA Negeri 3 Parepare in the 2021/2022 academic year. Data collection uses validated test sheets and interview guidelines. The data analysis used in this research is descriptive qualitative and the validity of the data uses triagulation techniques/methods. The subjects of this research were students in class The results of this research show that the difficulties experienced by students in solving trigonometry problems include difficulties understanding concepts, difficulties using principles, and difficulties with calculations. Factors that cause students to experience difficulties in solving trigonometry problems are the tendency for students not to understand the meaning of the questions, students not understanding trigonometry material, students not knowing formulas, students being less skilled in calculating operations, and students being accustomed to using calculators.